ANALYSIS OF THE EFFECTIVENESS OF APPLYING DISTANCE LEARNING MODELS DURING PANDEMI COVID-19 IN MEDAN CITY - R Wahyuni; D A Fazira; E S Hutasoit; T Lourenz; S Pardosi (UNIVERSITAS NEGERI MEDAN, 2021)
Based on Circular Number 4 of 2020 concerning the Implementation of Education Policies in the emergency period of the spread of the virus, the Minister of Education and Culture urges all educational institutions not to carry out the teaching and learning process directly or face-to-face, but must be done indirectly or remotely. The purpose of this study was to analyze the application of the distance learning model during the Covid-19 pandemic in the city of Medan. The method used in this research is descriptive method with a qualitative approach. The data collection technique uses an online questionnaire. From the results of the survey regarding the use of applications in the learning process, the most are using WhatsApp and Google Class Room. The process of delivering the respondent's subject matter answered sufficiently. The learning method used is the assignment and demonstration method. Assignments are given by the teacher via google form via the whatsapp group or via google class room. Based on the research results, it is concluded that the application of distance learning models (distance learning) cannot be said to be effective as long Covid-pandemic19 in the city of Medan because there were still many obstacles experienced by teachers in the learning process